Research on the implementation status and improvement strategies of cloud classroom personality teaching in elementary schools - Li Xiang Mao; Sri Leny (Universitas Negeri Yogyakarta, 2023)
Currently, the development of students' personality and the cultivation of innovative talents are regarded as an important task of education for each country, the personalized teaching has become the goal of the new curriculum reform in China. With the continuous development of cloud computing technology, network cloud platform education resources are being used more and more in the teaching process, the